AB0352 The Changing Face of Septic Arthritis Complicating Rheumatoid Arthritis in The Era of Biotherapies. Retrospective Single-Center Study over 35 Years. (15th July 2016) - Dubost, J.-J.; Pereira, B.; Tournadre, A.; Tatar, Z.; Couderc, M.; Soubrier, M.
Abstract : Background: Rheumatoid arthritis (RA) is a risk factor for septic arthritis (SA), and anti-TNF therapy doubles the risk of SA. Objectives: The purpose of this study was to see whether the frequency and features of SA complicating RA have changed over the last 35 years. Methods: This retrospective single-center study included the full register of all patients hospitalized at the rheumatology department of Clermont-Ferrand – CHU between 1979 and 2013 for septic arthritis bacteriologically documented by synovial fluid and/or blood culture samples. The periods 1979–2002 (period before biotherapies) and 2003–2013 (last decade in the era of biotherapies) were compared. Results: Between 1979 and 2013, 64/514 (12.5%) SA presented with a RA – 21/153 (13.7%) in the 2003–2013 period and 43/361 (11.9%) in the 1979–2002 period. Over the past decade, median age of SA–RA patients increased (61 vs 68 years; p <0.02) and predominant gender became males (52% vs 40%). The features of the RA remained unchanged: history (18 years (8–29) vs 16 (8–25)), rheumatoid factor (95% vs 87%), and corticosteroids (91% vs 81%) at the same mean dose (10 mg/d). 71% in the period before biotherapies and 63% in the last decade received a DMARD. Over the last decade 24% ( vs 0; p <0.003) of patients received a biologic DMARD: etanercept (n=2), adalimumab (n=1), rituximab (n=1), tocilizumab (n=1). Proportion of polyarticular infection had decreased (9.5% vs 37%; p <0.02), down to the same level as SA-non-RA cases (8%). Proportion of S. aureus infections had stabilized (62% vs 74%) in SA-RA patients but was higher than SA-non-RA (47% and 53%). MRSA infections became more frequent in SA-RA (31% vs 6%; p <0.05) in contrast to SA-non-RA cases (8% vs 16%; ns). Gram-negative bacilli infections have tended to become more frequent (19% vs 5%; p =0.08). Blood cultures less often tested positive (29% vs 47%; ns). Mortality rates has fallen slightly (5% vs 9%; ns), in contrast to SA-non-RA cases (7% vs 6%; ns). Conclusions: This study brings reassuring findings – in the era of biotherapies, the frequency of septic arthritis complicating rheumatoid arthritis has stabilized, and the most severe septic polyarticular forms are on the decline. Disclosure of Interest: None declared